Steric control over supramolecular polymer formation in trans-1,2-Bis(4-pyridyl)ethylene adducts of zinc xanthates: implications for luminescence - Kang, J.G.; Shin, J.S.; Cho, D.H.; Jeong, Y.K.; Park, C.; Soh, S.F.; Lai, C.S.; Tiekink, E.R.T. (American Chemical Society, 2010)
Steric control over supramolecular aggregation is demonstrated for a series of adducts formed between Zn(S2COR)(2) and trans-1,2-bis(4-pyridyl)ethylene, whereby supramolecular zigzag polymers are found when R is small, that is, Et (1) and n-Bu (2). but only bimetallic aggregates Could be formed when R = Cy (3). This results in different coordination geometries: four-coordinate N2S2 zinc in 1 and 2, and five-coordinate NS4 zinc in 3, a feature which greatly influences photophysical responses ill the solid State. When excited in the UV region, {Zn(St(2)COEt)(2)L}(infinity) (1) and {[Zn(S2COCy)(2)](2)L} (3) produce broad luminescence in the visible region. Five-coordinate 3 produces more broad and intense luminescence than four-coordinate 1. The configuration interaction singles (CIS) and post-Hartree-Fock (HF) calculations for 1 and 3 indicate the A-band excited state is responsible for the observed luminescence which is strongly associated with charge transfer from S and Zn.